PERTUMBUHAN DAN HASIL TANAMAN KANGKUNG DARAT ( Ipomoea reptans Poir) DENGAN PEMBERIAN MULSA JERAMI PADI - Remigius Ragung; I Made Suryana; Ni Putu Pandawani; I Ketut Sumantra; I Putu Sujana (Program Studi Agroteknologi Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2023)
Water spinach (Ipomea reptans Poir) is a vegetable plant that is widely traded and highly favored by consumers, kale contains vitamins A, B, C minerals and fiber, especially iron, and has an important meaning in fulfilling food nutrition. The use of mulch in the cultivation of horticultural crops is something that is absolutely necessary. There are so many benefits that are obtained by farmers, including easing the work of farmers in cleaning weeds. The research objectives were: (1) to determine the effect of the use of rice straw mulch on the growth and yield of land kale, (2) to determine the optimum dose of rice straw mulch on the growth and yield of land kale. This study used a Randomized Block Design (RBD) with 6 treatments which were repeated 4 times. The data were analyzed using ANOVA or analysis of variance and if they were significantly different, the LSD test was continued with 5%, to find out the best rice straw dose for each treatment, The use of straw mulch gave a significant effect on plant height, number of leaves, number of weeds, fresh weight of plant crown, fresh weight of plant roots, oven dry weight of plant crown and oven dry weight of plant roots, growth and yield of land Water spinach (Ipomoea reptans poir) at mulching straw with a weight of 500 g (M5) per polybag gave the highest yield with a fresh weight of 14.75 g of plant crown and 2.07 g of oven-dry weight of the plant canopy.